BRANDING USAHA DAPOER RENDANG RIRY - SUCI WULANDARI, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
This final project aims to maximize branding program, to raise product brand awareness and product brand image, and to make teenagers feel royal for traditional food. Branding Usaha Dapoer Rendang Riry have role to maximize, introduce, and, convince that this product is not only for old people but also young people. Branding use some visual communication design principles and elements. Data analysis method used is SWOT analysis to find the solution from the problem faced. Creative program used is AIDCA because it is appropriate the people habit and culture nowadays which is alongside and can not be separated with internet. Designing process start with data collection, interview, and observation toward Dapoer Rendang Riry products. Main media used for this branding is Brand Guide Line, and the supporting media are packaging, poster, x-banner, shirt, shopping bag, sticker, stationery set, appron, instagram, facebook.Keyword : Branding, traditional food, minangkabau